IDEOLOGI DAN KEBERPIHAKKAN MEDIA MASSA - Muttaqin, Ahmad (Fakultas Dakwah IAIN Purwokerto, 2011)
Differences in presenting reality through the news media are not merely technicaljournalism. Moreover, the differences represent ideology and interests of each media.Pluralist perspective views mass media as an entity that is neutral, objective, andquestionable. This is because the mass media in the modern era become an open area forvarious ideological battles to be won by one of them. It is the winner ideology thatdominates and determines the practices of mass media coverage.As a representation of ideology, the news presents the facts through the texts andthe languages that led to the conclusion in favor of a particular object. The goal is toorganize public attitudes and actions on an option that is economically and politicallybeneficial to the owners of mass media. The issue that is easy to see the practice ofrepresentation ideology is religion-related news. This is not separated from the centralposition of religion in some cases be a sensitive issue.